The role of β2-integrins and CD44 in intrahepatic leukocyte sequestration - Castro Santa, Edward; Salnikova, Olga; Ryschich, Eduard (Journal of surgical research, 2013)
Background - Intrahepatic leukocyte sequestration is a component of the systemic inflammatory response, and can be triggered by systemic immune dysfunction during sepsis. - Methods - To examine leukocyte sequestration over time during endotoxemia, its influence on liver function, and the role of specific cell adhesion molecules, endotoxemia was induced in mice by intraperitoneal application of lipopolysaccharides. Leukocyte sequestration was measured at different times after induction using fluorescence microscopy. Liver injury was evaluated by measuring liver enzymes and tissue histology. - Results - Endotoxin induces a strong leukocyte sequestration in the liver microvasculature. This was associated with an induction of liver injury, as reflected by an increase in enzyme levels and histomorphologic changes. Intrahepatic leukocyte sequestration was reduced in CD44−/−, but not in intercellular adhesion molecule-1 (ICAM-1)−/−, lymphocyte function-associated antigen-1−/−, and macrophage-1−/− antigen mice. Leukocyte sequestration dropped in ICAM-1−/−, lymphocyte function-associated antigen-1−/−, and macrophage-1−/− mice in later stages, but remained stable in wild-type and CD44−/− animals. Reduced leukocyte sequestration in CD44−/− mice was accompanied by a significant decrease in transferase levels. - Conclusions - Endotoxemia induces stable intra-sinusoidal leukocyte sequestration, which contributes to liver injury. At the initial stage of the endotoxemia, leukocyte sequestration depends on CD44 but is independent of ICAM-1 and β2-integrins. Intercellular adhesion molecule-1 and β2-integrins, but not CD44, stabilize leukocyte sequestration during the later stage of endotoxemia. The molecular modulation of intrahepatic leukocyte sequestration may have important therapeutic implications in sepsis, reducing liver injury, and improving immune defense capabilities.
Im Titel wird beta als griechischer Buchstabe dargestellt
Gesehen am 16.03.2021